Macromolecular chemistry-- 9 : Specially invited and selected symposium lectures presented at the International Symposium on Macromolecules held in Aberdeen, Scotland, 10-14 September 1973 - Cross, Lionel Charles (Macromolecular chemistry Specially invited and selected symposium lectures presented at the International Symposium on Macromolecules held in Aberdeen, Scotland, 10-14 September 1973, 1974)
Macromolecular Chemistry-9 provides information pertinent to the fundamental aspects of macromolecular chemistry. This book discusses the structure, properties, morphology, chemical reactions, and compatibility of polymers. Organized into 16 chapters, this book begins with an overview of the methods for the determination of polymer compatibility by means of the mutual solvent method and a light-scattering technique. This text then examines certain urethane systems that are suitable for application in products usually made of black reinforced rubber with cord reinforcement. Other chapters consi.